Aplikasi silica dalam bidang biomedis - Rahmatullah, Fikri Ardiansyah (Maliki Interdisciplinary Journal, 2024)
Silica (SiO2) is an inorganic compound abundantly found on Earth, with various applications in the biomedical field. As a material with a porous structure, silica exhibits high biocompatibility and stability. In nanomedicine, silica is utilized as a nanocarrier for drug delivery, enabling more effective treatments and reducing side effects. Additionally, silica is used in the production of glass-ceramics for prosthetic devices due to its superior bioactivity and mechanical properties. Silica-based aerogels have been modified into effective antibacterial agents and used as nerve scaffolds, promoting better nerve cell growth and efficient nerve repair. With its wide range of applications and numerous advantages, silica continues to be a highly promising material in the biomedical field.